Social Construction Analysis of the Phenomenon of Prostitution in Makassar City - Ridwan Ridwan; Fitriani Sari Handayani Razak; Umi Umairah Suhardi; Nurfadillah Nasiruddin; Ahmad Aminuddin; Andi Muhammad Ikbal Salam (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to analyze and understand the in-depth reasons why people in Makassar City tolerate the presence of commercial sex workers. Researchers seek to understand the meaning and connections of this social phenomenon from the perspective of those who interact with commercial sex workers (CSWs) daily. This research approach employs a phenomenological approach with qualitative analysis. The focus of this study is on the community living side by side with sex workers who work individually and are spread across several locations (segregation). The research locus specifically includes Jalan Veteran, Jalan Sungai Saddang, Jalan Nusantara, and Jalan Topaz, which are identified as segregated areas whose impacts are deeply felt by the surrounding community. The results significantly indicate that widespread apathy and moral decadence in society are the main factors creating a space for tolerance towards the presence of commercial sex workers. This tolerance is not merely passive acceptance, but rather a social construct shaped through various interactions and understandings of dynamic social realities.